2021
DOI: 10.1038/s41598-021-87807-6
|View full text |Cite
|
Sign up to set email alerts
|

Intravital imaging of real-time endogenous actin dysregulation in proximal and distal tubules at the onset of severe ischemia-reperfusion injury

Abstract: Severe renal ischemia-reperfusion injury (IRI) can lead to acute and chronic kidney dysfunction. Cytoskeletal modifications are among the main effects of this condition. The majority of studies that have contributed to the current understanding of IRI have relied on histological analyses using exogenous probes after the fact. Here we report the successful real-time visualization of actin cytoskeletal alterations in live proximal and distal tubules that arise at the onset of severe IRI. To achieve this, we indu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 27 publications
(28 reference statements)
3
59
0
Order By: Relevance
“…To this end, a variety of macroscopic and microscopic approaches have been used to evaluate whole kidney scaffold structure and function [8][9][10][11][12][13][14][15] . In several animal models, such techniques have shown that the decellularization process successfully removes native cellular/tissue components and decellularizing agents while retaining the vascular and ECM structures.…”
Section: Background and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, a variety of macroscopic and microscopic approaches have been used to evaluate whole kidney scaffold structure and function [8][9][10][11][12][13][14][15] . In several animal models, such techniques have shown that the decellularization process successfully removes native cellular/tissue components and decellularizing agents while retaining the vascular and ECM structures.…”
Section: Background and Summarymentioning
confidence: 99%
“…Qualitative and quantitative assessments of tissue autofluorescence, velocity within the microcirculation, and microarchitecture porosity of scaffolds were acquired in live rats on day 0, day 1, day 2, and day 7 after transplantation and compared to the native (non-transplanted) organs. This sophisticated imaging technology's ability to evaluate renal dynamics in vivo is documented extensively [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Our manuscript aims to highlight methods of monitoring cellular/subcellular processes in real-time within transplanted kidney scaffolds, which can be extended to other organ scaffold systems.…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Gene therapies are emerging to restore or counter malfunctioning genes in conditions adversely influencing a patient's quality of life without pharmacological intervention, radiotherapy, or surgery (Goswami et al, 2019). This form of therapy has made significant progress since this concept arose in the 1960s and 1970s (Friedmann, 1992;Niidome and Huang, 2002;Collins and Thrasher, 2015), but tragic failures in clinical settings (Uddin et al, 2020) along with pervasive obstacles related to nucleic acid delivery (Corridon et al, 2013;Collett et al, 2017;Shi et al, 2017;Kolb et al, 2018;van Haasteren et al, 2020;Corridon et al, 2021), have limited its progression. However, a recent and significant achievement in this field has come from the CRISPR-Cas system.…”
Section: Gene and Cell Therapiesmentioning
confidence: 99%
“…The incidence of kidney failure, otherwise known as end-stage renal disease (ESRD) is rising globally (Arikan et al, 2021;Kari et al, 2021). Unfortunately, there is no cure for this condition, which can develop form the progression of acute and chronic injuries (Hsu and Hsu, 2016;Kolb et al, 2018;Corridon et al, 2021). Currently, transplantation is the best option to treat ESRD.…”
Section: Introductionmentioning
confidence: 99%